DOUBLE BURDEN PADA PEREMPUAN DITINJAU DARI PERSPEKTIF HUKUM ISLAM (STUDI KASUS DI HOME INDUSTRY KERUPUK “DUA PUTRA” SINGGAHAN TUBAN) - Fahri, Herfin; Ulya, Vita Fitriatul (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2022)
The development of the times marked by the flow of globalization has also changed the human mindset. If in the past women were considered the second sex and only took part in the domestic sector, now there are many women who play a role equal to the position of men, for example with many women who are involved in the public sector, therefore the phenomenon of double burden or double burden. often afflicts women. This study aims to explore the double burden of female workers in the